Elementary Classroom Teachers' Self-Reported Use of Movement Integration Products and Perceived Facilitators and Barriers Related to Product Use - Roddrick Dugger; Aaron Rafferty; Ethan Hunt; Michael Beets; Collin Webster; Brian Chen; Jeff Rehling; Robert Glenn Weaver (MDPI AG, 2020)
Movement integration (MI) products are designed to provide children with physical activity during general education classroom time. The purpose of this study was to examine elementary classroom teachers' self-reported use of MI products and subsequent perceptions of the facilitators of and barriers to MI product use. This study utilized a mixed-methods design. Elementary classroom teachers (n = 40) at four schools each tested four of six common MI products in their classroom for one week. Teachers completed a daily diary, documenting duration and frequency of product use. Following each product test, focus groups were conducted with teachers to assess facilitators and barriers. MI product use lasted for 11.2 (Standard Deviation (SD) = 7.5) min/occasion and MI products were used 4.1 (SD = 3.5) times/week on average. Activity Bursts in the Classroom for Fitness, GoNoodle, and Physical Activity Across the Curriculum were most frequently used. Facilitators of and barriers to MI product use were identified within three central areas-logistics, alignment with teaching goals, and student needs and interests. Teachers were receptive to MI products and used them frequently throughout the week. When considering the adoption of MI products, teachers, administrators, and policy makers should consider products that are readily usable, align with teaching goals, and are consistent with student needs and interests.